Rapid acidolysis of benzyl group as a suitable approach for syntheses of peptides naturally produced by oxidative stress and containing 3-nitrotyrosine - Niederhafner, Petr; Šafařík, Martin; Brichtová, Eva; Šebestík, Jaroslav (Amino acids, 2016)
3-Nitrotyrosine (Nit) belongs to products of oxidative stress and could probably influence conformation of neurodegenerative proteins. Syntheses of peptides require availability of suitable synthon for introduction of Nit residue. Common phenolic protection groups are more acid labile, when they are attached to Nit residue. We have found that Fmoc-Nit(Bn)-OH is a good building block for syntheses of Nit containing peptides by Fmoc/tBu strategy. Interestingly, the peptides containing multiple Nit residues can be available solely by use of Fmoc-Nit(Bn)-OH synthon. Bn is removed rapidly with ca 80 % trifluoroacetic acid in dark. The cleavage of Bn from Fmoc-Nit(Bn)-OH proceeds via pseudo-first order mechanism with activation barrier 32 kcal mol(-1) and rate k = 15.3 s(-1) at 20 °C. This rate is more than 2,000,000 times faster than that for cleavage of benzyl from Tyr(Bn).
Keywords: Trifluoroacetic Acid; Nitrotyrosine; Peptide synthesis; oxidační stres; hydrolýza; alpha-Synuclein; sekvence aminokyselin; Oxidative Stress; Tyrosine; kyselina trifluoroctová; Reaction rate; Amino Acid Sequence; Fluorenes; Prions; peptidy; Alpha-synuclein; Hydrolysis; fluoreny; tyrosin; alfa-synuklein; priony; Peptides